STRATEGI PEMASARAN STAFF MARKETING DALAM MENARIK CALON JEMAAH PADA AET TRAVEL INTERNATIONAL PT. PENJURU WISATA NEGERI PADANG - Elsa Miftahul Huda; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
The Thesis Entited Marketing Strategy of Marketing Staff In Attracting of Prospective pilgrims at AET Travel International PT. Padang Country Tourism Direction ( Case Study: AET Travel International PT. Padang Country Tourism Direction NAME ELSA MIFTAHULHUDA Nim 3619079 hajj and Umrah Management Study Program (MHU), Faculty of Islamic Economic and Business (FEBI), State Islamic University (UIN). This research is motivated by Marketing Staff in attracting the interest of prospective pilgrims to Umroh or Hajj at AET Travel and Compete with other Travels which currently has also been promoting the advantages of their Travel to attract prospective pilgrims. Coupled with that at that time there was an outbreak of Covid-19 which caused the travel party to not be able to send the congregation. After the Covid outbreak is over and quarantine is over, then Hajj and Umroh flights can be reopened. But the price of the package after Covid has increased slightly from the airlane. And inaddition, people may not trust or believe in going for umroh or Hajj due to conditions that are currently dangerous. That’s where travel travel agent compete to be able to reassure the public to go for Umrah with the best price offers and facilities provided by travel agent, resulting in intense competition between travel parties. The purpose of this research is to determine the right Strategy taken by AET Travel International PT. Direction of State Tourism in attracting the interest of prospective pilgrims. This research is a qualitative descriptive analysis research with a descriptive approach. Where data collection techniques used observation, in-depth, interview and documentation. The result of this study obtained strategies that can be taken by AET Travel International PT. Padang Country Tourism Direction to attract prospective pilgrims, Namely : 1 Offline Promotion Strategy, AET Travel applies an offline Strategy directly including : Brochures, personal selling. 2 AET Travel Padang Online Promotion Strategy are carried out in the form of : Website, Social Media.